Survey of Interest in Football in Children Aged 12-15 Years in Tulehu Village - Irfan Albakia; W. Unmmehopa; Siti Divinubun (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this research is to obtain information about Interest in Football in Children Aged 12-15 Years in Tulehu Village. This research is a quantitative descriptive research, meaning that it is a research that is used to find out the actual situation based on the results of a questionnaire with valid and reliable instruments. According to Creswell (in Duli, 2019) provides a brief definition of quantitative research, namely a type of research that explains phenomena by collecting numerical data which is analyzed using math-based methods, especially statistics. The method used to collect data is a survey method. The instrument used was a questionnaire. From the table above it can be seen that the determination of statement items is said to be valid when the rcount is rtable. To determine the rtable value, it can be seen in the r product moment table at a significant level of 5% and the number of respondents (n) is 40 people or n 40, so that the rtable is 0.301. Based on the table above, there are 8 invalid statements, so that 32 statements are used in the questionnaire. interest in playing soccer in early childhood 12-15 years in Tulehu Village is relatively high with a percentage reaching 94.25%. Which is influenced by several indicators of interest such as feelings of pleasure, interest, attention, involvement and othersrds: